Peningkatan Kompetensi Pedagodik Guru Melalui Kegiatan KKG Pai Untuk Menghadapi Tantangan Era Digital - Mufidah Hayati; Zulfani Sesmiarni (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
This study aims to explore and analyze various efforts in developing the professionalism of Islamic Religious Education teachers who are able to overcome the challenges of education in the digital era through the activities of the Islamic Religious Education Working Group (KKG PAI). This type of research is descriptive qualitative. Data were obtained from the results of observations, interviews, and documentation, then analyzed by reviewing, reducing data, and then interpreting data. The results of the study indicate that KKG (Teacher Working Group) is a forum formed to improve teacher competence and professionalism, both inside and outside the classroom. To find out the implementation of the program being implemented, of course, an evaluation program is needed with elements of context, input, process, and product. The components of the context evaluation are: 1) whether the KKG PAI program is a must for Islamic Religious Education teachers; 2) what is the purpose of the KKG PAI program; 3) who are the targets of the KKG PAI program. The elements of input evaluation are: (1) human resources; (2) supporting facilities and infrastructure; (3) funds; and (4) regulations. Basically, the process evaluation is to find out to what extent the plan has been implemented and what components need to be improved. Product evaluation is an assessment carried out in order to see the achievement or success of a program in achieving previously set goals. From the results of observations that have been made, the KKG program in an effort to improve teacher competence in facing the challenges of the digital era can be implemented in the future.